I need the correct answer to this problem and an explanation on how to work these type of questions. please help.

6-2x/x-3

= -2x+6/x-3

= -2(x-3)/(x-3)

= -2*1 since (x-3) cancels each other

= -2 (Answer)

Tutors, please sign in to answer this question.

Atlanta, GA

6-2x/x-3

= -2x+6/x-3

= -2(x-3)/(x-3)

= -2*1 since (x-3) cancels each other

= -2 (Answer)

Longmont, CO

6-2x/x-3 . The 6-2x can be changed to 2*(3-x) by factoring out the 2

(2*(3-x))/(x-3) = . Then you can factor out a -1 so that you have -2*(x-3)

((-2)*(x-3))/(x-3) =

-2*((x-3)/(x-3)) = . The (x-3)'s cancel each other out and you are left with x=-2

-2*1 = -2

((-2)*(x-3))/(x-3) =

-2*((x-3)/(x-3)) = . The (x-3)'s cancel each other out and you are left with x=-2

-2*1 = -2

- Algebra 2 3503
- Algebra 5059
- Math 9863
- Prealgebra 172
- Algebra Word Problem 2488
- Algebra Help 967
- Geometry 1907
- Math Help 5447
- Word Problem 5121
- Precalculus 1586